ANALISIS KEANEKARAGAMAN JENIS TUMBUHAN BAWAH DI HUTAN LINDUNG JOMPI - Lies Indriyani; Alamsyah Flamin; Erna Erna (Jurnal Ecogreen, 2017)
Analysis of Biodiversity of Understorey Plants in Jompi Protected Forest was held in Wali Village, Watopute district in Muna Regency, Southeast Sulawesi Province. This study was conducted in August-November 2015. The objective of this  study is to determine the types of understorey plants and how the level of species biodiversity in Jompi Protected Forest. This study was by using a purposive sampling method. Analysis of the vegetation was by using line method terraced. Sampling unit measuring 2m x 2m plot, the number of sample plots altogether are 30 plots, with a distance of 200 meters each path were arranged systematically.The results found that the species of understorey plants in Jompi Protected Forest are 31 species in 18 families. The kind that has a density, frequency and the index value of the highest importance are the type of signal grass (Brachiaria decumben). Total value of species diversity index (H ') of understorey plants in the Jompi Protected Forest is  2,99 (very high abundance). Keywords: Jompi protected forest, understorey plants, biodiversity